Level of knowledge and practice of safe medication use among visitors at Hospital Sultan Abdul Halim: a cross-sectional study - Muhammad Ridzwan Ramond, Nur Jemaima (2018)
Good knowledge and practice of medication use can improve one's health. The major objective of this study is to evaluate the current level of knowledge and practice of safe medication use among the visitors in Hospital Sultan Abdul Halim (HSAH). A cross-sectional survey was given out to visitors that were waiting in the hospital's lobby at HSAH and this study was conducted from October 2017 to January 2018, which is over 4 months. Visitors who were 18 years and above and understand Bahasa Melayu were included. The data was then analysed by using SPSS version 16. This study was focused to find whether gender and chronic disease are significantly associated with the level of knowledge and practice of safe medication use, to find whether there is an association between education level and practice of finishing their treatment regimens and to find the relationship between level of knowledge and practice of safe medication use. This study showed that the visitors have a high level of knowledge (mean ± SD = 11.24 ± 2.50) and good practice of safe medication use (mean ± SD = 62.44 ± 6. 79). However, there was less awareness in some aspects in knowledge of medication use and inappropriate practices of using medication safely, in terms of not telling their physician about other medication that they are taking and using the same medication based on symptoms experienced due to past illness. It also found out that only presence of chronic disease is significantly associated with the level of knowledge and practice of safe medication use, while gender does not. Other than that, it shows that there is an association between education level and practice of finishing their treatment regimens. There is also an association between the practice of sharing medication and the practice of using the same medication to cure similar symptoms